Optically Modulated Multiband Terahertz Perfect Absorber. Issue 12 (30th September 2014) - Seren, Huseyin R; Keiser, George R; Cao, Lingyue; Zhang, Jingdi; Strikwerda, Andrew C; Fan, Kebin; Metcalfe, Grace D; Wraback, Michael; Zhang, Xin; Averitt, Richard D
<x xml:space="preserve">Abstract</x> Development of tunable, dynamic, and broad bandwidth metamaterial designs is a keystone objective for metamaterials research, necessary for the future viability of metamaterial optics and devices across the electromagnetic spectrum. Yet, overcoming the inherently localized, narrow bandwidth, and static response of resonant metamaterials continues to be a challenging endeavor. Resonant perfect absorbers have flourished as one of the most promising metamaterial devices with applications ranging from power harvesting to terahertz imaging. Here, an optically modulated resonant perfect absorber is presented. Utilizing photo‐excited free carriers in silicon pads placed in the capacitive gaps of split ring resonators, a dynamically modulated perfect absorber is designed and fabricated to operate in reflection. Large modulation depth (38% and 91%) in two absorption bands (with 97% and 92% peak absorption) is demonstrated, which correspond to the LC (0.7 THz) and dipole (1.1 THz) modes of the split ring resonators.